Dichotomous strategies? The migration of Whimbrels breeding in the eastern Canadian sub‐Arctic. Issue 4 (27th October 2016) - Johnson, Andrew S.; Perz, Johanna; Nol, Erica; Senner, Nathan R.
Abstract: The conservation of migratory birds requires internationally coordinated efforts that, in turn, demand an understanding of population dynamics and connectivity throughout a species' range. Whimbrels ( Numenius phaeopus ) are a widespread long‐distance migratory shorebird with two disparate North American breeding populations. Monitoring efforts suggest that at least one of these populations is declining, but the level of migratory connectivity linking the two populations to specific non‐breeding sites or identifiable conservation threats remains unclear. We deployed light‐level geolocators in 2012 to track the migration of Whimbrels breeding near Churchill, Manitoba, Canada. In 2013, we recovered 11 of these geolocators, yielding complete migration tracks for nine individuals. During southbound migration, six of the nine Whimbrels stopped at two staging sites on the mid‐Atlantic seaboard of the United States for an average of 22 days, whereas three individuals made nonstop flights of 8000 km from Churchill to South America. All individuals subsequently spent the entire non‐breeding season along the northern coasts of Brazil and Suriname. On their way north, all birds stopped at the same two staging sites used during southbound migration. Individuals staged at these sites for an average of 34 days, significantly longer than during southbound migration, and all departed within a 5‐day period to undertake nonstop flights ranging from 2600 to 3100 km to the breeding grounds. These extended spring stopovers suggest that female Whimbrels likely employ a mixed breeding strategy, drawing on both endogenous and exogenous reserves to produce their eggs. Our results also demonstrate that this breeding population exhibits a high degree of connectivity among breeding, staging, and wintering sites. As with other long‐distance migratory shorebirds, conservation efforts for this population of Whimbrels must therefore focus on a small, but widely spaced, suite of sites that support a large proportion of the population.